2009
DOI: 10.1111/j.1365-2915.2009.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

A long‐lasting topical deltamethrin treatment to protect dogs against visceral leishmaniasis

Abstract: To develop long-lasting, topical pour-on insecticides for dogs to control zoonotic visceral leishmaniasis, two deltamethrin-based formulations (emulsifiable concentrate [EC] and suspension concentrate [SC]) were tested for their efficacy against the phlebotomine sandfly Lutzomyia longipalpis Lutz & Neiva (Diptera: Psychodidae), vector of Leishmania infantum Nicolle (Kinetoplastida: Trypanosomatidae). The entomological outcomes tested were anti-feeding effect (proportion of female sandflies unfed), lethal effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 58 publications
0
22
0
1
Order By: Relevance
“…Limitations in diagnostic sensitivity likely lead to false-negative diagnoses for a large number of asymptomatic dogs, delays between testing and dog removal increase the likelihood of transmission, and the financial and emotional costs of the policy implemented in Brazil are high (329,339,340). The use of permethrin or deltamethrin collars or topical applications has shown efficacy in reducing sandfly feeding and transmission in areas of endemicity (341,342). However, the cost and necessity for reapplication make these interventions more difficult to utilize in many regions of endemicity.…”
Section: Preventionmentioning
confidence: 99%
“…Limitations in diagnostic sensitivity likely lead to false-negative diagnoses for a large number of asymptomatic dogs, delays between testing and dog removal increase the likelihood of transmission, and the financial and emotional costs of the policy implemented in Brazil are high (329,339,340). The use of permethrin or deltamethrin collars or topical applications has shown efficacy in reducing sandfly feeding and transmission in areas of endemicity (341,342). However, the cost and necessity for reapplication make these interventions more difficult to utilize in many regions of endemicity.…”
Section: Preventionmentioning
confidence: 99%
“…longipalpis densities in the first seven days after intervention, but did not increase the dispersion of vector to the sprayed border areas. Although some studies reported deltamethrin residual effects up to 9-12 months inside houses 13,19 , strong anti-feeding effects when applied to dogs as collars or topically, and repellent effects in impregnated bednets 7,8,9 , and pyrethroids as lambdacyalothrin reducing impact on Lu. longipalpis sand fly captures after focal or indoor applications 14,18 , there are many reports about the short or transient effects of fenitrothion 14 , cypermethrin 12 and deltamethrin as peridomestic sprayed insecticide 1,13,22,36 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the model is capable of suggesting spraying intervention at only one of the two site types (either at houses or at cattle sheds). Even though insecticides have the dual effect of anti-feeding and of mortality, 21,31 this model only considers the mortality effect. In our future research, we plan to extend the framework by incorporating the above features as well as influences of an anti-feeding effect on the sprayed sites and dynamic variation in sandfly population as it changes due to seasonal conditions and reduces over time after insecticide intervention.…”
Section: Discussionmentioning
confidence: 99%
“…20 Moreover, the appropriate empirical studies were used to estimate P. argentipes' insecticide-induced mortality, 24 hours after spraying with DDT 12 and deltamethrin. 16 An insecticide's lethal effect is assumed to decay exponentially over time 21 as suggested in the literature. The decay rates inside houses 16 and cattle sheds 22 were then estimated using data from the literature (the procedure is shown in Supplemental Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation